Rancang Bangun Pompa Air Aliran Aksial Pipa Pvc 5 Inci Berpenggerak Motor Listrik - Rendi, Rendi; Firman, Muhammad; Hartadi, Budi (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Axial pumps are one type of pump that is widely used for industrial purposes to move fluids from low places to higher places with large capacities. The axial pump has very complicated components so it has a very expensive price. This study aims to design and build an axial flow pump with a 5-inch PVC pipe casing driven by an electric motor. The design process begins with the determination of pump specifications including the capacity of the fluid you want to flow and the height of the fluid you want to move, then proceed with calculations including the capacity of the electric motor, shaft, and bearings, then proceed with the process of making components according to the calculations that have been done and the final stage is the process assembly and testing. The result of the calculation is that for an axial pump specification with a maximum head of 0.5 m, a pipe diameter of 0.14 m, and a maximum capacity of fluid that can flow 0.02 m3/s, a ½ Hp motor is required with a drive shaft diameter of 10 mm. The test results show that the pump can operate properly, the water capacity that can be moved is 0.0138 m3/s for the variation in the number of blades 2 and 0.0161 m3/s for the variation in the number of blades 3. So the efficiency for the variation in the number of blades 2 is 46.54% and for blade 3 is 54.53%